2014
DOI: 10.1007/s13277-014-2887-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma interleukin-35 levels predict poor prognosis in patients with non-small cell lung cancer

Abstract: Interleukin-35 (IL-35) has recently been implicated in tumor immunity. The aim of this study was to explore the clinical role of plasma IL-35 in patients with non-small cell lung cancer (NSCLC). Plasma collected from 106 patients with NSCLC cases and 78 healthy controls (HC) were subjected to IL-35 enzyme-linked immunosorbent assay (ELISA) and relationships between plasma IL-35 levels and clinical characteristics were evaluated. The correlation of IL-35 and overall survival was analyzed using Kaplan-Meier meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 20 publications
4
28
1
Order By: Relevance
“…High expression of IL-35 in tumor tissues and the elevated plasma IL-35 levels have been reported in patients with solid or hematopoietic malignancy [10, 11, 36]. The increase of IL-35 in tumor could promote tumor progression as shown by our data and others [37].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…High expression of IL-35 in tumor tissues and the elevated plasma IL-35 levels have been reported in patients with solid or hematopoietic malignancy [10, 11, 36]. The increase of IL-35 in tumor could promote tumor progression as shown by our data and others [37].…”
Section: Discussionsupporting
confidence: 76%
“…Clinical evidences showed that the higher expression of p35 and EBI3 was detected in tumor tissues [9]. The elevated serum IL-35 levels correlated with poor prognosis in patients with renal cell carcinoma and non-small cell lung cancer [10, 11]. Given that a chronic inflammatory microenvironment is an essential component of all of tumors [1], it is possible that IL-35 may promote tumor development by facilitating chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…While no significant association was identified in the present study, an insufficient number of cases may have contributed to this lack of significance. In previous studies, over-expression of IL-35 in peripheral blood has been recognized as an unfavorable prognostic factor for malignant tumors, including nasopharyngeal carcinoma, pancreatic ductal adenocarcinoma, colorectal and non-small cell lung cancer (14,21,28,29). Nevertheless, another study detected increased IL-35 expression in early stage breast cancer and non-metastatic cases (27).…”
Section: The Association Between Il-35 Expression and The Prognosis Omentioning
confidence: 98%
“…7D, F The aberrant expression of IL-35 has been shown in different cancers including acute myeloid leukemia [27,28], prostate cancer [18], breast cancer [19,29], colorectal cancer [17,30], pancreatic ductal adenocarcinoma [31], gastric cancer [32], and hepatocellular carcinoma [33]. Gu et al [21]. showed that plasma IL-35 expression was elevated and was a promising potential predictor in prognosis of clinical outcome of NSCLC patients.…”
Section: Il-35 Suppressed the Function Of Cd8mentioning
confidence: 99%
“…In addition, elevated IL-35 levels are also associated with cancer progression, aggressiveness, and recurrence [17][18][19][20]. A previous study also demonstrated that IL-35 overexpression correlated with a poor prognosis in patients with NSCLC [21]. However, the role of IL-35 in NSCLC has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%